THE USE OF REALISTIC MATHEMATICS EDUCATION TO APPROACH AS AN EFFORT TO IMPROVE MATH COMMUNICATION SKILLS - Romadhon Kuswantoro; Abdul Taram (Universitas Ahmad Dahlan, 2020)
Problems about the low mathematical communication skills of students are still found in Junior High School (SMP) Muhammadiyah 2 Minggir. Based on the problem above, the researcher is interested in research to improve students' mathematical communication skills using the Realistic Mathematics Education (RME) inset material to class VII of SMP Muhammadiyah 2 Minggir in the academic year 2019/2020. The type of research used in this study is classroom action research (CAR). This study's subject was students grade VII class B of SMP Muhammadiyah 2 Minggir in 2019/2020, consisting of 29 students. This study's object is implementing the mathematics learning process through Realistic Education Learning approaches to improve students' mathematical communication skills. Data collection techniques used by researchers are observation, tests, and interviews. After obtaining the data, then the data is processed by triangulation techniques and calculated using Microsoft Excel. Based on the calculation results of mathematical communication skills in students grade VII class B of SMP Muhammadiyah 2 Minggir, which have been measured with indicators of mathematical communication abilities, the average percentage of mathematical communication abilities of students in the first cycle is 59%, which is included in the excellent category. The percentage increased to 75.19% in the second cycle or after being given an action using a learning approach to realistic mathematic educations with the category